Serum Extracellular Vesicle–Derived miR-124-3p as a Diagnostic and Predictive Marker for Early-Stage Acute Ischemic Stroke - Qi, Zheng; Zhao, Yingying; Su, Yu; Cao, Bin; Yang, Jian-Jun; Xing, Qinghe (Frontiers in Molecular Biosciences, 2021)
Background: A delay in the diagnosis of acute ischemic stroke (AIS) reduces the eligibility and outcome of patients for thrombolytic therapy. Therefore, early diagnosis and treatment of AIS is crucial. The present study evaluated the sensitivity and accuracy of serum extracellular vesicle (EV)-derived miR-124-3p in the diagnosis and prediction of AIS. Methods: miRNA expression profile was downloaded from Gene Expression Omnibus (GEO) database and analyzed by R software. EVs were harvested from the serum of AIS patients using a total exosome isolation kit and characterized by Western blot, transmissionelectron microscope, and nanoparticle tracking analysis. BV2 microglia were pre-stimulated with lipopolysaccharide (LPS), followed by miR-124-3p treatment for 24 h and subsequent analysis of viability, apoptosis, and migration (scratch assay) and Western blotting. The relative expression of the selected genes was assessed by qRT-PCR. The phosphorylation of Erk1/2, PI3K/Akt, and p38MAPK in BV2 microglia cells was evaluated by Western blotting, while the luciferase reporter gene assay detected the correlation between key genes involved in pro-inflammatory signaling pathways and miR-124-3p. Results: hsa-miR-124-3p was downregulated in AIS serum compared to the non-AIS serum (p<0.05), and the gene expression of has-miR-124-3p in EVs was negatively correlated with serum pro-inflammatory cytokines and NIHSS (p<0.05). In addition, miR-124-3p promoted the viability and inhibited the apoptosis of LPS-induced BV2 microglia. Furthermore, miR-124-3p reduced the phosphorylation of Erk1/2, PI3K/Akt, and p38MAPK and promoted the migration in LPS-induced BV2 microglia (p<0.05). Conclusion: Serum EV-derived miR-124-3p serves as a diagnostic and predictive marker for early-stage AIS.